Efektivitas Pemungutan Retribusi Tempat Rekreasi Taman Margasatwa Ragunan Terhadap Pendapatan Retribusi Daerah Provinsi DKI Jakarta Tahun 2022 - Khoerudin, Miftah Farid; Inayati, Inayati (Jurnal Administrasi dan Kebijakan Publik, 2024)
This study aims to analyze the effectiveness of levy collection at Ragunan Wildlife Park in 2022 and its contribution to the Regional Revenue (PAD) of DKI Jakarta Province. Levy collection is an important source of income for the local government; however, there are several challenges affecting its effectiveness, such as stagnant ticket prices since 2011 and issues with the JakCard payment system. The research employs a descriptive qualitative method, with data collection through observation, interviews, and documentation. Informants were selected using purposive sampling. The findings show that the effectiveness of levy collection at Ragunan Wildlife Park in 2022 was 77%, which is considered fairly effective, although there are still some obstacles. The factors affecting effectiveness include unadjusted levy rates in line with economic developments and technical issues with the JakCard payment system that disrupt the transaction process. Therefore, it is recommended that the local government review levy rates and improve the payment system to enhance the effectiveness of levy collection and its contribution to the PAD of DKI Jakarta Province.